Assessing the structure and moneytary values of trees for sustainable land use in Kuching North City Council - Siti Meliah, Binti Sebli Joney (Universiti Malaysia Sarawak (UNIMAS), 2013)
Street trees are important features and asset to the city. Trees and roadside ecosystems are assets that fix carbon, provide shade, filter air and protect from wind, and provide wildlife corridors and habitat. By assigning monetary value to the street trees, it could help initiated the policy makers to recognize the potential benefits of trees to ensure decisions made are consistent to sustainable urban planning) This study focuses on the trees structure and its monetary value for sustainaole land use in North Kuching City Council. The economic values of the trees planted in Tun Abdul Rahman Yaakub road were estimated using Thyer Tree Valuation Method. Trees species surveyed were Khaya senegalensis, Samanea saman, Peltophorum pterocarpum, Pterocarpus indicus, Swietenia macrophylla, Tabebuia Wallid and Lagerstroemia jloribunda." Approximately 26% of trees heights were below 15m and 14% were more than 21 meters. The distribution of trees dbh showed nearly 60% of tree planted in Tun Abdul Rahman Yaakub are in functional period (> 77cm). Khaya senegalensis has the highest mean economic value estimated at RM 165473.65 followed by Samanea saman which estimated at RM 115 468.43. The lowest estimated value of tree species surveyed was Peltophorum pterocarpum valuated at RM 5763.15.